U.S. public television in the digital era: from niche to “Greek marketplace”? - Hélène Palmeri (Transatlantica)
Motivated by the renewed interest for public media in the United States since 2008, as well as the return of a futuristic philosophical bent in official speeches, we examine the reality of public media 2.0 and the place of public television in the context of Obama’s America. Are the contradictions and the problems inherited from the liberal tradition really surpassed? We first look into how public television emerged in the U.S., with what missions, financing and structures, then in the second part we study what is left today of the initial ideal and whether or not current conditions are favorable to public media. We conclude that there are few signs which allow us to say that the Obama administration and Congress are implementing a reform worthy of the name. Indeed policy questions are dominated by much more powerful actors. Nevertheless the numerous reports published since 2008, emanating for the most part from the academic sector, have the merit to relaunch the debate on public media and democracy in the Internet era.